Water Conservation Ecological Service Function and Its Value Response Mechanism in a Nested Water Conservancy Project Area - Zeng, Chunfen; Qi, Wanyu; Mao, Yuqing; Liu, Rui; Yu, Boya; Dong, Xinning (Frontiers in Environmental Science, 2022)
The Three Gorges Project is the largest water conservancy project in the world. To cope with the ecological problems of the subsidence zone in the Three Gorges Reservoir area, the Kaizhou water level regulating dam was built, forming a model of nested water conservancy projects. The Pengxi River Basin is affected not only by this project but also by human activities in the reservoir area and changes in the substratum and hydro-meteorology, which exert influences on the water connotation function and its ecological value through complex mechanisms. In addition, the response mechanism of the changes the environment is unclear. Therefore, based on the integrated valuation of ecosystem services and tradeoffs (InVEST) model and a spatial interpolation method, in this study, two time nodes (2005 and 2018) before and after the operation of the nested water conservancy projects began were selected and seven simulation scenarios with different water levels, precipitations, and temperatures were created to explore the evolution of the water conservation service function in the nested water conservancy project operation area under the complex changes in the environment. The results reveal that the operation of the water conservancy projects has had some influence on the water content, but the response of the water content function to the precipitation conditions has been more significant. In colder and rainier years, the water content was higher. In contrast, the lowest value occurred in a year with high temperatures and low rainfall. The highest and lowest values were quantitatively different. Therefore, the influences of the complex environmental factors on the regional water connotation service function deserve more attention. The results of this study provide a scientific basis for research on the ecological service function and the value of water conservation in the Three Gorges Reservoir subsidence zone and the nested operation area of the related water conservancy projects, as well as a data reference for the optimal allocation of regional water resources.